ANALYSIS OF APHASIA SUFFERED BY COMEDIAN SONY WAKWAW IN DIGIDIVA YOUTUBE CHANNEL ENTITLED “BISA SEBUT NAMA SAYA?”: A PSYCHOLINGUISTIC APPROACH - Rindiana Prasetianti (ReALL - Research on Applied Linguistics and Literature, 2023)
Aphasia is a language disorder that is experienced by many people. Aphasia is a communication disorder caused by damage to the part of the brain that controls language. Therefore, this study aims to develop an understanding of Aphasia, a language disorder. The writer chose Sony Wakwaw, a comedian from Indonesia as the object of this research. Sony Wakwaw has had Aphasia since he was a child which is caused by the high fever he often experiences. This condition has attracted the interest of writer to explore the aphasia disorder experienced by Sony Wakwaw, with a focus on identifying the type of aphasia that occurs and its impact on his daily life. In analyzing the types of aphasia experienced by Sony Wakawaw, the writer refers to Ardila's theory, in which aphasia is classified into two main types, namely Wernicke's Aphasia and Broca's Aphasia. The data for this study were taken from the utterances uttered by Sony Wakwaw in the video entitled "Bisa Sebut Nama Saya?" which was uploaded on the Digidiva YouTube channel. This study used a qualitative descriptive method, which allowed researchers to gain an in-depth understanding of Sony Wakwaw's experiences in dealing with the aphasia disorder.